Pengelolaan Instagram @Pemkotbogor Sebagai Media Komunikasi Digital Publik oleh Humas Sekretariat Daerah Kota Bogor - Aliya Salsabila; Hudi Santoso (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
The Regional Secretariat of Bogor City, through the Protocol and Leadership Communication Division (Prokompim), utilizes social media as a medium for public communication, focusing on the Instagram account @pemkotbogor. This study aims to analyze how the account is managed as a communication medium by the Public Relations Division and to identify the communication model applied using the Circular Model of SoMe for Social Communications (Share, Optimize, Manage, Engage). Using a qualitative descriptive method with interviews, observations, and literature studies, the research found that @pemkotbogor is managed systematically through information sharing, content optimization, account management, and public engagement. The implementation of this model has made Instagram an effective platform for disseminating government policies, promoting official activities, and strengthening the city government's positive image. Overall, the account’s management has been effective and supports two-way communication between the government and the public, though improvements are still needed in real-time interaction and creative content development to enhance engagement.